Face extraction in mobile phones - Loo, Zing Zai (2016)
Face detection and face recognition are very much discussed topics these days. However, there is an intermediate process often being forgotten, commonly referred to as face extraction. Face extraction is a crucial step performed before faces can be recognised accurately. It also open doors to more advanced face-related applications to be developed, such as face expression analysis, age estimation and 3D face modelling.